The Pre-service Biology Teachers' Understanding on Organic and Inorganic Waste Management - Enggar Utari; Fadlullah Fadlullah; Wahyu Badarudin; Nurkholis Nurkholis (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The study aimed to determine the understanding of the pre-service biology teachers regarding the importance of organic and inorganic waste management for the environment. The method used is a qualitative using questionnaire data collection method. The results showed that the pre-service biology teachers' understanding of organic and inorganic waste management was very high. However, there still needs to be more understanding of how to manage waste properly and its application.